2014
DOI: 10.1016/j.paid.2013.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity mediates the association between borderline personality pathology and body mass index

Abstract: Borderline personality disorder (BPD) is associated with obesity, a major risk factor for a number of chronic illnesses (e.g., cardiovascular disease). We examined whether impulsivity and affective instability mediate the association between BPD pathology and body mass index (BMI). Participants were a community sample of adults ages 55–64 and their informants. The Structured Interview for DSM-IV Personality measured BPD symptoms and the Revised NEO Personality Inventory measured self- and informant-report impu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 37 publications
(54 reference statements)
0
15
0
1
Order By: Relevance
“…It would be interesting to reanalyse these effects for ION to understand if these outcomes pertain to trait Impulsiveness as the underlying attribute, or something more specific (cf. Iacovino et al, ; Terracciano et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It would be interesting to reanalyse these effects for ION to understand if these outcomes pertain to trait Impulsiveness as the underlying attribute, or something more specific (cf. Iacovino et al, ; Terracciano et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, not all N5: Impulsiveness items relate to BMI. Terracciano et al () specify that
the Impulsiveness scale effect [on BMI] was due to two items specific to the eating domain (‘When I am having my favorite food, I tend to eat too much’ and ‘I sometimes eat myself sick’) (p. 685).
Although this may seem to provide little evidence for trait Impulsiveness being associated with BMI, follow‐up studies have still concluded that Impulsiveness relates to BMI without testing the crucial role of the two aforementioned items behind this association (Sutin, Costa, et al, ; Sutin et al, , ; see Iacovino, Powers, & Oltmanns, , for a notable exception).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with prior work (Iacovino, Powers, & Oltmanns, ; Whiteside & Lynam, ), we calculated impulsivity scores by taking the average of NEO‐PI‐R impulsiveness (from neuroticism), excitement‐seeking (from extraversion), deliberation (from conscientiousness; reverse scored), and self‐discipline (from conscientiousness; reverse scored). All facets had small to moderate correlations (.27–.57; all p < .001), except for self‐discipline with excitement‐seeking ( r = .02, p = .57).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, although impulsivity decreased with age in BPD, it continued to result in these negative consequences. BPD has also been found to predict arthritis and heart disease, in which obesity accounts for some of the variance in this relationship [ 44 , 54 ].…”
Section: Waxing and Waning Course Of Bpd From Childhood To Old Agementioning
confidence: 99%